Inocellia rara sp. nov. (Raphidioptera: Inocelliidae), a new snakefly species from Taiwan, with remarks on systematics and biogeography of the Inocelliidae of the island - Liu, Xingyue; Aspöck, Horst; Aspöck, Ulrike (Zootaxa, 2014)
A new species of the snakefly genus Inocellia Schneider, 1843 from Taiwan is described: Inocellia rara sp. nov. It represents the third species in the family Inocelliidae and the first record of the Inocellia fulvostigmata species group from Taiwan.